Convecção natural de fluidos de lei de potência e de Bingham em cavidade fechada preenchida com meio heterogêneo - Lavarda, Jairo Vinícius (2015)
Many studies have been carried out in square enclosures with generalized Newtonian fluids with natural convection in past few years for directly applications in compact heat exchangers, cooling of electronics systems and polymeric engineering. The natural convection in square enclosures with differently heated sidewalls, filled with power-law and Bingham fluids in addition with heterogeneous medium and centered block are analyzed in this study. The heterogeneous medium are solid, square, disconnected and conducting blocks. The parameters used are the Rayleigh number in the range 104 - 107 , power index n range of 0, 6 - 1, 6, Bingham number range of 0, 5 - Bimax , being the influence of Prandtl number investigated for each fluid model. The number of blocks for heterogeneous medium are 9, 16, 36 and 64, keeping constant solid to fluid conductive ratio, κ = 1. For enclosures with centered block are used the nondimensional block size from 0, 1 to 0, 9, with solid to fluid conductive ratio in range κ = 0, 1; 1 and 10. Mathematical modeling is done by mass, momentum and energy balance equations. The solution of equations have been numerically solved in ANSYS FLUENT R software. Firstly, numerical solutions for validation with Newtonian fluids in clean enclosures are conducted, followed by enclosures with heterogeneous medium and centered block. Subsequently, numerical solutions of power-law and Bingham fluids with same enclosures configurations are conducted. The results are reported in the form of streamlines, isotherms and average Nusselt number at hot wall. In general, the heat transfer process in enclosure is governed by Rayleigh number, size and thermal conductivity of the blocks, power index n for power-law fluid and Bingham number for Bingham fluid. Both fluid models are very sensitive with Prandtl number changes. Heterogeneous medium decrease heat transfer in enclosure when affects thermal boundary layer for both fluid models. One analytical prediction was made for power-law fluid. An increase in heat transfer occurs with low thermal conductivity block and few interference and with high thermal conductivity block and great interference, for both fluids.